Recent micro-earthquake activity at Northern Evoikos gulf, Central Greece - PAPANASTASSIOU, D.; STAVRAKAKIS, G.; MAKARIS, D. (Bulletin of the Geological Society of Greece, 2001)
During the last 4 months of 1999, the Institute of Geodynamics, of the National Observatory of Athens, deployed in the area of north Evoikos gulf, a local seismic network of 5 digital stations equipped with sensitive 3-components seismometers. The recorded micro-earthquakes, located in the upper part of the crust, show that there is significant seismic activity in the area of northern Evoikos gulf. This activity could be correlated not only with the main faults of the area, which are the Atalanti fault and the fault running parallel to the coasts of Evia island but also with other faults which are assumed to be, till now, less active or not so important.